2019
DOI: 10.4314/ajesms.v15i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pre-service teachers’ mathematics self-efficacy and their mathematics achievement

Abstract: This study sought to explore the relationship between pre-service teachers’ perceived self-efficacy in teaching mathematics and their achievement in mathematics. It is a descriptive study which involved forty students (47.5% male, 52.5% female) of Kibi College of Education. Data was collected through a Mathematics Self-Efficacy Scale (MSES) questionnaire and a Mathematics Achievement Test (MAT). The findings of the study revealed a strong positive relationship between the pre-service teachers’ self-efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Mathematics is seen as an essential precursor to success in modern society and it is a challenge for most students (Chu et al, 2017). In Ghana, as in most African countries, mathematics is taught at the basic school, senior high school (SHS) as well as colleges of education (CoE) curricula (Ampofo, 2019). Mathematics is a compulsory subject for every learner at these levels of education and is a gateway and critical filter for further studies in the country (Ampofo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematics is seen as an essential precursor to success in modern society and it is a challenge for most students (Chu et al, 2017). In Ghana, as in most African countries, mathematics is taught at the basic school, senior high school (SHS) as well as colleges of education (CoE) curricula (Ampofo, 2019). Mathematics is a compulsory subject for every learner at these levels of education and is a gateway and critical filter for further studies in the country (Ampofo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, as in most African countries, mathematics is taught at the basic school, senior high school (SHS) as well as colleges of education (CoE) curricula (Ampofo, 2019). Mathematics is a compulsory subject for every learner at these levels of education and is a gateway and critical filter for further studies in the country (Ampofo, 2019). The student's ability to cope with mathematics improves one's chance of social improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematics was perceived as an essential precursor to success in modern society. Its usefulness was visible in sciences, technological innovations, commerce for economic developments and educational advancement of any nation (Tella, 2008;Ampofo, 2019). The roles played by Mathematics in the primary school, Junior and Senior Secondary School (JSS and SSS) as well as Colleges of Education (COE) cannot be underscored.…”
Section: Introductionmentioning
confidence: 99%
“…It is a compulsory subject for every learner at these levels. In actual fact, it is a gatekeeper and critical filter for further studies (Ampofo, 2019). Salman, Yahaya and Adewara (2011) observed that Mathematics seemed to be the most terrifying subject by pupils and students due to figure-phobia related challenges they are being confronted with.…”
Section: Introductionmentioning
confidence: 99%